Filogeografia comparada dos anuros endêmicos da Mata Atlântica Dendropsophus elegans (Anura, Hylidae) e Chiasmocleis spp. (Anura, Microhylidae) - Tonini, João Filipe Riva (2011)
A considerable number of data sets have been published on the phylogeography and distribution patterns of Atlantic forest organisms. Some phylogeographic breaks are consistently observed across taxa, such as those existing along the São Francisco and Doce rivers, as well as a secondary break in the southern region of the biome, close to Paranapanema river. Studies using climatic data to infer paleo distributions of Atlantic forest taxa incorporated a predictive component to phylogeographic studies in Brazil. Furthermore, provided scenarios that it was possible to test the hypothesis of demographic expansion of Atlantic forest taxa associated with glacial and interglacial periods in the Pleistocene. When investigating the demographic history of taxa now inhabiting cold and high altitude areas, there was a demographic expansion during the Pleistocene. However, the taxa that inhabit lowland forests, it was observed that shrank its distribution during the Pleistocene and showed demographic expansion from north to south after the end of the last glacial. Here I use endemic taxa of the Atlantic forest (Dendropsophus elegansand some representative species of the genus Chiasmocleis) to study local phylogeographic patterns and to investigate the historical and ecological processes underlying the structure of the populations sampled and the observed patterns. To this end, I used 148 specimens of D. elegansand 92 samples of Chiasmocleisspp., all of which had a portion of the mitochondrial gene ND2 sequenced. The results show that both taxa corroborate the hypothesis already describe in the literature of the existence of high levels of haplotype diversity between San Francisco and Doce rivers, and less stable areas insouthern Atlantic forest. However, samples from areas in the southern region of the Atlantic showed signs of demographic expansion and low levels of haplotype diversity. Samples from areas of higher altitude, inside or outside climatically stable areas proposed by other authors, showed that local populations have remained isolated for a long time and accumulated genetic differences. This differs from the processes inferred for populations that currently inhabit the lowland forests, which have suffered population contraction during the last glacial maximum and expanded in the intergacial. In Chiasmocleis, phenotypically distinct species were grouped into a single clade, although both morphospecies also be reciprocally monophyletic. This may represent a possible hybridization event,that may have occurred due to secondary contact between individuals of both morphospecies or a recent diversification with retention of ancestral polymorphism. However, the molecular clock showed that the divergence between clades is very old (14.5 Myr) to accept the hypothesis of recent diversification